THE USAGE OF E-BOOKS IN HIGHER EDUCATION LEARNING - Alif Fathi B Md. Noor, Muhamad; Abdullah, Suhaila (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The rise of high end device had made most of the user especially higher education student shift from using the normal thick book to electronic books or well known as e-books. Thus, this paper aims to examine the issues of current usage of e-books in the higher education learning. The issues will be regarding the definitions related to e-books, why do the higher education student really need to utilize e-book throughout their learning, the studies made regarding the usage of e-books inside and outside the country and the facing problems in dealing with e-books. By implementing the e-books in learning, students or may be the instructors will face a new era of which they will find that learning can be made simple, and more efficient plus the knowledge could be easily accessible by the grasp of our hand.Keyword: e-book, reading, higher education